Architecture of Modeling Process of Flexible Manufacture Systems Actions - Nasirova, E.A. (Herald of Azerbaijan Engineering Academy, 2022)
Formalization of the process and activity of system engineering design of technical systems a comparative analysis of artificial intelligence systems, their descriptive models and tools is carried out. Based on the comparative analysis, the main research issues of the article were identified. The architecture of the process of modeling the functioning of flexible manufacture systems (FMS) and their mechatronic means is proposed.